Alemtuzumab as Antirejection Therapy: T Cell Repopulation and Cytokine Responsiveness. Issue 6 (June 2016) - Bouvy, Anne P.; Klepper, Mariska; Betjes, Michiel G.H.; Weimar, Willem; Hesselink, Dennis A.; Baan, Carla C.
Abstract : Background: Alemtuzumab induction therapy in kidney transplant patients results in T cell depletion followed by slow immune reconstitution of memory T cells with reduced immune functions. The kinetics and functional characteristics of T cell reconstitution when alemtuzumab is given during immune activation, ie, as antirejection therapy, are unknown. Methods: Patients (n = 12) with glucocorticoid-resistant or severe vascular kidney transplant rejection were treated with alemtuzumab. Flow cytometric analysis was performed on whole blood to measure cell division by the marker Ki-67, and cytokine responsiveness by IL-2–mediated and IL-7–mediated phosphorylation of signal transducer and activator of transcription 5 of T cells before and during the first year after rejection therapy. Results: At 1 year after alemtuzumab antirejection therapy, the total T cell population recovered to baseline level. Repopulation of CD4+ and CD8+ T cells was associated with increased percentages of Ki-67+ proliferating T cells ( P < 0.05). In addition, both populations showed a phenotypic shift toward relatively more memory T cells ( P < 0.01). At the functional level, IL-7 reactivity of CD4+ memory T cells was diminished, reflected by a decreased capacity to phosphorylate signal transducer and activator of transcription 5 during the first 6 months after alemtuzumab treatment ( P < 0.05), whereas reactivity to IL-2 was preserved. CD8+ T cells were affected in terms of both IL-2 and IL-7 responses (both P < 0.05). After reconstitution, relatively more regulatory T cells were present, and a relatively high proportion of Ki-67+ T cells was observed. Conclusions: Preliminary data from this small series suggest that alemtuzumab antirejection therapy induces homeostatic proliferation of memory and regulatory T cells with diminished responsiveness to the homeostatic cytokine IL-7. IL-2 responsiveness was affected in repopulated CD8+ T cells. Abstract : Supplemental digital content is available in the text.